Thomas Rudborne, monk of Winchester, and the council of Florence - Greatrex, Joan G. (Studies in church history, 1972)
One of the ways in which historians show their wisdom is by their reluctance to make general, definitive pronouncements. Is there anyone among us, for example, who can say with certainty that the spirit of ecumenism abroad today is deeper and more prevalent than in any preceding age? The history of ecumenical councils is the history of the Church’s constant striving to reconcile heretics and end schism. Furthermore, it is surely not true to say that concern for the unity of Christendom has been confined in the past only to the small group of council delegates who for spiritual, theological and often, unfortunately, political reasons were, so to speak, professionally involved. However, before I am anathematised for expounding on a negative generalisation let me hasten to draw your attention to the ecumenical interests of Thomas Rudborne, O.S.B.